Analisis Kepuasan Konsumen Menggunakan Customer Satisfaction Index (CSI) Pada Ayam Penyet Sangar Bogor - Diah Ayu Ningrum; Ramadhan Rizal Rahman; Witya Syamaratul Jannah; Mochammad Ikhsan; Khoirul Aziz Husyairi; Tina Nur Ainun (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The development of micro, small and medium enterprises (MSMEs) is currently growing, with the existence of these MSMEs it can encourage Indonesian economic activities, and has a significant influence. One indicator that these MSMEs are progressing or developing is by assessing how satisfied consumers are in getting their satisfaction in purchasing products. Therefore, this study aims to assess how the level of consumer satisfaction in purchasing ayam penyet sangar products, this study uses the Customer Satifisfication Index (CSI) method. in the results of the calculations that have been carried out, there are final results that show a CSI value of 85.13% which indicates a very satisfied indicator. with the results obtained, this business is in accordance with what is expected by consumers because of the value of the calculation results.